PENGARUH ECONOMIC VALUE ADDED DAN MARKET VALUE ADDED TERHADAP RETURN SAHAM PADA PT. HANJAYA MANDALA SAMPOERNA PERIODE 2013 - 2022 - Ricky Ardiansyah; Kartono (Journal of Research and Publication Innovation, 2025)
This research aims to determine the effect of Economic Value Added and Market Value Added on Return at PT. Hanjaya Mandala Sampoerna Tbk for the period 2013-2022. This research method uses quantitative with an associative approach. based on the t test results obtained that Economic Value Added has a tcount value of 7,422 > ttable 2,36462 and a significant value of 0,000 < 0,05, this means that Economic Value Added partially has a posisitve and significant effect on Return, while Market Value Added has a tcount value of 4,365 > ttabel 2,36462 and a significant value of 0,014 < 0,05. This shows that Market Value Added partially has a posisitve and significant effect on Return. The results of the f test, obtained a fcount value of 27,741 > Ftable 4,74 with a significant value 0,000 < 0,05. This shows that Economic Value Added and Market Value Added simultaneously have a positive and significant effect on Return.